A self-made portable separation device based on 2-D MOF nanosheets for the efficient separation of dyes in solutions. Issue 22 (18th May 2021) - Li, Anqi; Ma, Xiaofan; Ma, Jie; Yuan, Qingyi; Zhang, Jun; Xuan, Xiaopeng
Abstract : Herein we reported a simple and economical method for fabricating a portable separation device based on 2D-MOF nanosheets, which can be used disposably for a special purpose due to the low cost, simple manufacturing process in an emergency. Abstract : Herein we reported a simple and economical method for fabricating a portable separation device based on exfoliated 2D-metal–organic framework (2D-MOF) nanosheets. This device is composed of a layered Cu-MOF as a filter and a syringe filter as the holder. Benefiting from the structural characteristic of the 2D-MOF nanosheets, the separation experiment reveals that this strategy can exhibit high efficiency and selectivity for dyes with different sizes. This device can be used disposably for a special purpose due to the low cost, simple manufacturing process in an emergency.